2020
DOI: 10.1177/0972150920915330
|View full text |Cite
|
Sign up to set email alerts
|

Do Local Investors Exhibit Smart Value Investment? Empirical Evidence from India

Abstract: We have studied the investment behaviour of ‘foreign institutional investors’ (FIIs) and ‘domestic institutional investors’ (DIIs) in the Indian stock market for positive feedback trading and smart money value investments. We have collected the daily investment of FII and DII in Indian stock markets along with NIFTY daily returns. We have used multivariate causality approach VAR and found that FII investments follow positive feedback trading approach whereas DII follow smart money value investments in the Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Empirical evidence suggests that higher frequencies tend to return more evidence in support of their feedback trading, thus denoting that foreign funds employ such strategies for short-horizon investments. On balance, most studies confirm foreign funds' momentum trading in emerging markets, including Brazil (Gonçalves and Eid, 2017), India (Arora, 2016;Hiremath and Kattuman, 2017;Chauhan and Chaklader, 2020), Malaysia (French, 2017;Liew et al, 2018), South Korea (Kim and Wei, 2002b;Choe et al, 2005;Oh et al, 2008;Kim et al, 2009;Jeon and Moffett, 2010;Hong and Lee, 2011;Ikizlerli et al, 2019), Taiwan (Chang, 2010;Chiang et al, 2012;Liao et al, 2013;Hsieh, 2013), Thailand (Phansatan et al, 2012;French, 2017) and Vietnam (Vo, 2017). As per developed markets, similar evidence surfaces in Finland Keloharju, 2000, 2001;Do et al, 2008), Germany (Baltzer et al, 2019), Japan (Karolyi, 2002;Kamesaka et al, 2003;Hood et al, 2013) and Sweden (Dahlquist and Robertsson, 2004); this pattern is also confirmed in crossmarket studies at the regional (Kaminsky et al, 2004;Hsieh et al, 2011;Chakraborty and Kakani, 2016) and global (Froot et al, 2001;Choi and Skiba, 2015;Kanas and Karkalakos, 2017) levels.…”
Section: Empirical Evidencementioning
confidence: 83%
“…Empirical evidence suggests that higher frequencies tend to return more evidence in support of their feedback trading, thus denoting that foreign funds employ such strategies for short-horizon investments. On balance, most studies confirm foreign funds' momentum trading in emerging markets, including Brazil (Gonçalves and Eid, 2017), India (Arora, 2016;Hiremath and Kattuman, 2017;Chauhan and Chaklader, 2020), Malaysia (French, 2017;Liew et al, 2018), South Korea (Kim and Wei, 2002b;Choe et al, 2005;Oh et al, 2008;Kim et al, 2009;Jeon and Moffett, 2010;Hong and Lee, 2011;Ikizlerli et al, 2019), Taiwan (Chang, 2010;Chiang et al, 2012;Liao et al, 2013;Hsieh, 2013), Thailand (Phansatan et al, 2012;French, 2017) and Vietnam (Vo, 2017). As per developed markets, similar evidence surfaces in Finland Keloharju, 2000, 2001;Do et al, 2008), Germany (Baltzer et al, 2019), Japan (Karolyi, 2002;Kamesaka et al, 2003;Hood et al, 2013) and Sweden (Dahlquist and Robertsson, 2004); this pattern is also confirmed in crossmarket studies at the regional (Kaminsky et al, 2004;Hsieh et al, 2011;Chakraborty and Kakani, 2016) and global (Froot et al, 2001;Choi and Skiba, 2015;Kanas and Karkalakos, 2017) levels.…”
Section: Empirical Evidencementioning
confidence: 83%
“…The budget 2021 was purely growthoriented and thus, we could see a huge influx of foreign capital whereas domestic investors were on a selling spree to book profits. It is reported that FIIs follow a positive feedback trading strategy and DIIs follow a contrarian feedback trading strategy (Sehgal and Tripathi, 2009;Chauhan and Chaklader, 2020). Therefore, it is worthwhile to analyze the behavior depicted by FIIs and DIIs in the equity segment of the Indian capital market around the budget day.…”
Section: Foreign Flows and Domestic Flowsmentioning
confidence: 99%
“…Also, we can see that the trading strategy adopted by FIIs in the pre-and post-budget longterm period does though not have a significant difference at the 5% level but it is significant at the 10% level of significance. Further, it is noticed that foreign investors indulge in making the market returns deviate from their fundamental value by overreacting to the news/shocks/events (Chauhan and Chaklader, 2020;(Ananthanarayan et al, 8-9 June 2009;? ;Dhingra et al, 2016) Table 6 depicts that there exists an insignificant difference in the net investment pattern of DIIs in the pre-and postbudget periods.…”
Section: Foreign Flows and Domestic Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant contemporaneous relationship was established between FII flows and volatility of stock markets (Lakshmi & Thenmozhi, 2018). FIIs increased volatility in the Indian stock markets by higher inflows during the period of better expected returns (Chauhan & Chaklader, 2020). The impact of FII trading activities on the Indian market volatility was more significant compared to DII (Gahlot, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%